Socially Responsible Behaviors of Nursing Students in Private Universities in Santiago, Chile: A Study on the Alignment with Sustainable Development Goals - Iturra-Gonzalez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Universities, particularly in nursing education, have evolved to incorporate University Social Responsibility (USR) into their curricula, emphasizing ethical, social, and sustainable competencies, which align with the Sustainable Development Goals (SDGs) to enhance healthcare and education. The study examines socially responsible behaviors, ethical competencies, and sustainability values among nursing students in private universities in Santiago, Chile, and their relation to sociodemographic variables. Methods: The study measures social responsibility in nursing students at private universities, accredited and co-financed by the State in Santiago, Chile, using the ICOSORE-U questionnaire, with statistical analyses such as EFA and CFA to validate the scale and evaluate correlations with sociodemographic variables. Results: The study validated the ICOSORE-U-10 scale for social responsibility in Chilean nursing students through both exploratory and confirmatory factor analysis. The results revealed a two-factor structure and an acceptable internal reliability (α = 0.841), with no significant differences related to sociodemographic variables. The findings confirmed that socially responsible behaviors are positively correlated with the development of ethical competencies and sustainability among these students. Conclusions: the socially responsible behaviors of nursing students are mainly determined by their orientation towards University Social Responsibility (USR) and not by sociodemographic variables. This orientation favors the development of ethical and professional competencies, improving their ability to address social and ethical challenges in the health field. Integrating the principles of USR in university education is key to training professionals committed to social justice, equity and sustainability in health care. © 2025 by the authors.